Heat treatment studies on activated carbon and charcoal for carbon nanotube synthesis - Tee, Jia Chee; Buang, Nor Aziah; Aziz, Madzlan; Sanip, Suhaila M.; Ismail, Ahmad Fauzi (2003)
The discovery of carbon nanotubes (CNT) in 1991 by Iijima has captured the attention of researchers worldwide. CNT are formed by rolled graphite sheets, with an inner diameter starting from 1 nm up to several nm and length of 10 - 100 nm. Hydrogen is the cleanest, sustainable and renewable energy carrier, and hydrogen energy system is expected to replace the existing fossil fuels in the future. In particular, one potential use of hydrogen lies in powering zero-emission vehicles via a fuel cell. The discovery of the high and reversible hydrogen storage capacity of CNT makes such a system very promising. The BET surface area and composition of Activated Carbon and Charcoal were studied, as suitable carbon sources for CNT synthesis. The materials were heat treated at high temperatures (600 and 800 "C) under nitrogen gas with various dwelling time (4, 8, 12 and 15 hours). The morphology and composition studies were done by Scanning Electron Microscope (SEM) and Energy Dispersive X-ray Analysis (EDAX) respectively. The surface area analyses were carried out using nitrogen gas adsorption technique. The morphology and surface texture of the carbon materials also showed significant improvement after heat treatment. The samples treated pnder N2 atmosphere maintained its high carbon content. Both activated carbon and charcoal showed an increase in their BET surface area after the heat treatment. Therefore as a result, the activated carbon and charcoal are potential carbon sources for the synthesis of CNT.